Perceptions of physiotherapists towards research: a mixed methods study. Issue 2 (June 2016) - Janssen, J.; Hale, L.; Mirfin-Veitch, B.; Harland, T.
Abstract: Objectives: To explore the perceptions of physiotherapists towards the use of and participation in research. Design: Concurrent mixed methods research, combining in-depth interviews with three questionnaires (demographics, Edmonton Research Orientation Survey, visual analogue scales for confidence and motivation to participate in research). Setting: One physiotherapy department in a rehabilitation hospital, consisting of seven specialised areas. Participants: Twenty-five subjects {four men and 21 women, mean age 38 [standard deviation (SD) 11] years} who had been registered as a physiotherapist for a mean period of 15 (SD 10) years participated in this study. They were registered with the New Zealand Board of Physiotherapy, held a current practising certificate, and were working as a physiotherapist or physiotherapy/allied health manager at the hospital. Main outcome measure: The primary outcome measure was in-depth interviews and the secondary outcome measures were the three questionnaires. Results: Physiotherapists were generally positive towards research, but struggled with the concept of research, the available literature and the time to commit to research. Individual confidence and orientation towards research seemed to influence how these barriers were perceived. Conclusion: This study showed that physiotherapists struggle to implement research in their daily practice and become involved in research. Changing physiotherapists' conceptions of research, making it more accessible and providing dedicated research time could facilitate increased involvement in the physiotherapy profession.